Role of plasma ascorbic acid in nasal allergy- a review - Munjal, Manish; Singh, Atul; Khurana, Ajit Singh; Munjal, Shubham; Mehta, Arnav; Shukla, Khyati; Waraich, Gurkaran (International Journal Of Community Medicine And Public Health, 2020)
Ascorbic acid plays a pivotal role in common cold and allergic rhinitis by affecting the innate and adaptive immunity It antagonizes mediators of allergic rhinitis like histamine, prostaglandins etc. It also maintains the normal redox potential of the cells preventing bonding of antibody to antigen. It helps in stress conditions and has stimulatory effect on interferon synthesis. The present study was undertaken to study the role of plasma ascorbic acid in patients suffering from nasal allergy.